Genetic polymorphisms of TRPA1 does affect risk of cisplatin induced nephrotoxicity in Chinese population - Cong Wang; Guifei Deng; Siyu Niu; Xianglong Meng (Translational Oncology)
Introduction: Irreversible acute kidney injury (AKI) caused by cisplatin limits its clinical use, and transient receptor potential anchor protein 1 (TRPA1) regulates cisplatin-induced nephrotoxicity (CIN) through NF-κB signaling pathway-mediated inflammation. Single nucleotide polymorphisms in TRPA1 and NF-κB1 genes may be associated with individual heterogeneous nephrotoxicity. Materials and methods: In this paper, we investigated the association of 17 single nucleotide polymorphisms (SNP) of TRPA1 and NF-κB1 genes with cisplatin-induced acute nephrotoxicity. Nephrotoxicity and its severity were assessed according to the Common Terminology Criteria for Adverse Events (CTCAE 5.0). SNPs were measured by 48-Plex SNPscan® high-throughput SNP typing echnology in DNA isolated from peripheral blood of 589 Chinese Han lung cancer patients (241 with CIN and 348 without CIN) treated with cisplatin regimen. Results: TRAP1 gene rs920829 locus T allele carriers had a reduced risk of nephrotoxicity relative to C allele carriers (OR 0.684, 95 % CI 0.524–0.894, p = 0.003), and their additive and dominant models showed similar trends as well. However, the SNPs of NF-κB1 were not observed to be correlated with nephrotoxicity. Conclusion: SNPs of TRPA1 have the potential as biomarkers for predicting cisplatin nephrotoxicity.